Microbiological quality of municipal tap water and filtered drinking water in Serdang, Selangor - Mahmud @ Ab Rashid, Nor Khaizura; Ahmad, N. A.; Ahmad Zainal, A. S.; Mahyudin, Nor Ainy (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Microbiological quality is one of the primary indicators of the safety of drinking water supply. Contaminated municipal and drinking water may result in waterborne diseases like gastrointestinal illness or diarrhea. The microbiological quality of tap water from municipal water supplies and drinking water from water cooler were comparatively studied. Heterotrophic plate count (HPC) and total coliform (TC) were enumerated from both samples that collected from Serdang area. The method used in this study for water analysis was membrane filtration (MF) method with using acetate cellulose membrane filter (0.45 mm). The heterotrophic plate count was found not significantly different (p > 0.05) in municipal tap water (MTW) and filtered drinking water (FDW), which was 1.60 log10 cfu ml-1 and 1.45 log10 cfu ml-1, respectively. For total coliform, MTW (1.44 log10 cfu ml-1) were found significantly (P ≤ 0.05) higher compared to FDW (1.00 log10 cfu ml-1). Heterotrophic plate count in MTW and FDW among the samples were not significantly different (p > 0.05) with the range value is 1.51 to 1.71 log10 cfu ml-1 and 1.01 to 1.65 log10 cfu ml-1 respectively. In conclusion, FDW possesses lower heterotrophic plate count and total coliform count than MTW, and microbiological quality of the drinking water system depends on regular cleaning of filters in the water cooler to ensure the safety of the water cooler users.